SYNERGISTIC APPROACH OF AYURVEDIC PRINCIPLES AND LIFE STYLE MODIFICATIONS TO COMBAT PSYCHOSOMATIC DISORDERS (International Journal of Ayurveda and Pharma Research, 2018)
The modern world has come to a challenge where most of the untreated conditions are resulting into complications and are burdened over society. To fetch all these, physicians are trying to limit such conditions by applying various scientific theories and methods to explain the basic underlying mechanism of health and diseases. Understanding of physical conditions through psychological approach is the mainstream of such conditions and is termed as Somatoform disorders or psychosomatic illnesses as explained by World Health Organization in international Statistical Classification of Diseases and Related Health Problems. Stress is the contributing factor that doesnt allow the individual to remain in harmony with the surroundings and threatens the bodys ability to maintain homeostasis. Dietary changes, mind-body therapies including meditation, stress relaxation techniques and Yoga can bring harmony back to individual suffering from such disorders.